Work From Anywhere, Perlukah ?: Tinjauan Praktis Lingkungan Kerja Terhadap Kinerja Pegawai Selama Pemberlakukan WFH - Nur Afifah (Journal Business Administration: Entrepreneurship and Creative Industry, 2023)
Work from Anywhere (WFH) is a new concept that was combined after the implementation of the Work Form Home scheme in early 2021 which aims as an effort to minimize the spread of Covid-19 globally. Employees are required to adapt the pattern of working from home that was previously done from the office. In addition, the work environment during the implementation of the WFH scheme is also taken into account for employee performance. This research aims to determine the effect of the Work Environment on employee performance at the State Wealth Service Office and Banda Aceh Auction. This research uses quantitative methods with a correlational approach. The research sample numbered 50 respondents with Nonprobability sampling technique with a saturated sampling approach. The method of collecting data in this study uses questionnaires collected directly by filling out the questionnaire sheet. Data analysis using simple linear regression, test t. accepted hypothesis means that there is a significant influence between Work Environment Variables and Employee Performance Variables. The results of the determination coefficient (R2) test obtained a figure of 31.6%. This means that the variation in the Employee Performance variable can be explained by the Work Environment variation of 31.6%, the remaining about 68.4% is explained by other variables not used in this regressionÂ model.